Composite cathode material, method for preparing the same, and all-solid-state lithium battery comprising the same
Patent Information
- Application Number
- CN202310042179.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-01-12
- Publication Date
- 2026-09-25
- Estimated Expiration
- 2043-01-12
AI Technical Summary
[0004]然而,将未修饰的镍钴锰酸锂正极活性材料与硫化物固体电解质混合制备的复合正极材料,在电池循环过程中会发生严重的界面反应,导致电池界面阻抗急剧增大,进而限制全固态电池的可逆比容量的发挥,致使电池循环稳定性恶化
[0033]本公开通过铌酸锂层、磷酸锂层与含磷的硫化物固体电解质层的配合,得到了一种结构及组分稳定,离子传输效率高的复合正极材料。具体而言,通过在铌酸锂层与含磷的硫化物固体电解质层之间形成磷酸锂保护层,既抑制了镍钴锰酸锂与硫化物固体电解质的界面反应,保证了镍钴锰酸锂结构及组分的稳定,又使得固体电解质均匀包覆在镍钴锰酸锂外部,增大了正极活性材料与固体电解质的界面接触面积和接触稳定性,提高了离子传输效率,从而使得采用该复合正极材料组装成的全固态锂电池具有良好的倍率性能和循环稳定性。
Smart Images

Figure CN117255150B_ABST
Abstract
Description
Technical Field
[0001] This disclosure belongs to the field of lithium battery technology, specifically relating to a composite cathode material, its preparation method, and an all-solid-state lithium battery containing the same. Background Technology
[0002] Lithium-ion batteries are widely used in numerous fields, including portable electronics, electric vehicles, and grid storage. For future electric vehicles with extended driving ranges, higher energy density is required, but the energy density of commercial lithium-ion batteries has reached its limit. Furthermore, leakage and thermal instability of the highly flammable liquid electrolyte pose serious safety concerns for commercial lithium-ion batteries. To address these issues, all-solid-state lithium battery technology is widely considered one of the most promising candidate technologies.
[0003] Sulfide solid electrolytes have 10 -3 ~10 -2 S·cm -1 The high ionic conductivity, near-1 lithium-ion transference number, and good machinability of lithium nickel cobalt manganese oxide (LiCO) allow for easy formation of an electrolyte / electrolyte interface with low interfacial impedance via room-temperature mechanical cold pressing. This interface also facilitates the assembly, fabrication, and performance optimization of all-solid-state batteries. Due to the synergistic effect of multiple metals, LiCO exhibits significant advantages in energy density and cycle stability. Combining sulfide solid electrolytes with LiCO cathode active materials to assemble all-solid-state batteries represents a feasible strategy for achieving high-performance all-solid-state batteries.
[0004] However, composite cathode materials prepared by mixing unmodified lithium nickel cobalt manganese oxide cathode active material with sulfide solid electrolytes undergo severe interfacial reactions during battery cycling, leading to a sharp increase in interfacial impedance and thus limiting the reversible specific capacity of all-solid-state batteries, resulting in deteriorated battery cycle stability. While composite cathode materials prepared by mixing coated lithium nickel cobalt manganese oxide cathode active material with sulfide solid electrolytes show some mitigation of interfacial side reactions, the poor solid-solid contact hinders ion transport, resulting in poor rate performance of the assembled all-solid-state lithium batteries.
[0005] Therefore, how to prevent the interfacial reaction between lithium nickel cobalt manganese oxide cathode active material and sulfide solid electrolyte, and ensure ion transport at the interface between the two, so as to improve the rate performance and cycle stability of lithium-ion batteries, is an urgent problem to be solved in this field. Summary of the Invention
[0006] To address the shortcomings of existing technologies, the present disclosure aims to provide a composite cathode material, its preparation method, and an all-solid-state lithium battery containing the composite cathode material. This composite cathode material can suppress the interfacial reaction between lithium nickel cobalt manganese oxide and the sulfide solid electrolyte, ensuring the stability of the lithium nickel cobalt manganese oxide structure and composition. It also increases the interfacial contact area and contact stability between the two, improving ion transport efficiency. Therefore, the all-solid-state lithium battery prepared using this material exhibits both good cycle stability and rate performance.
[0007] To achieve this objective, the present disclosure adopts the following technical solution:
[0008] In a first aspect, this disclosure provides a composite cathode material, which has a core-shell structure and comprises, from the inside out, lithium nickel cobalt manganese oxide particles, a lithium niobate layer, a lithium phosphate layer, and a phosphorus-containing sulfide solid electrolyte layer.
[0009] This disclosure discloses a composite cathode material with stable structure and composition and high ion transport efficiency by combining a lithium niobate layer, a lithium phosphate layer, and a phosphorus-containing sulfide solid electrolyte layer. Specifically, by forming a lithium phosphate protective layer between the lithium niobate layer and the phosphorus-containing sulfide solid electrolyte layer, the interfacial reaction between lithium nickel cobalt manganese oxide and the sulfide solid electrolyte is suppressed, ensuring the stability of the structure and composition of lithium nickel cobalt manganese oxide. Furthermore, the solid electrolyte is uniformly coated on the outside of the lithium nickel cobalt manganese oxide, increasing the interfacial contact area and contact stability between the cathode active material and the solid electrolyte, thereby improving ion transport efficiency. This results in all-solid-state lithium batteries assembled using this composite cathode material exhibiting excellent rate performance and cycle stability.
[0010] In some embodiments of this disclosure, the lithium nickel cobalt manganese oxide is selected from LiNi m Co n Mn 1-m-n One or more of O2;
[0011] Wherein, 0.5≤m<1 (for example, it can be 0.5, 0.6, 0.7, 0.8, 0.9, 0.95 or 0.98, etc.), and 0.5≤m+n≤1 (for example, it can be 0.5, 0.6, 0.7, 0.8, 0.9 or 1, etc.).
[0012] In some embodiments of this disclosure, the phosphorus-containing sulfide solid electrolyte is selected from x(Li) a G)·y(T c D d One or more of )·z(P2S5);
[0013] Where 0 ≤ x < 100, 0 ≤ y < 100, 0 ≤ z < 100;
[0014] a = 1 or 2, c = 1 or 2, d = 1, 2 or 5;
[0015] Element G is S, Cl, Br, or I;
[0016] Element T is Li, Si, Ge, P, Sn, or Sb;
[0017] Element D is Cl, Br, I, O, S, or Se;
[0018] And Li a G, T c D d Unlike P2S5, the stoichiometry of Li, P, and S is not zero.
[0019] In some embodiments of this disclosure, the phosphorus-containing sulfide solid electrolyte is selected from Li 6-i P 1+j S 5-i Cl 1+i , Li6PS5Cl, β-Li3PS4, Li7P2S8I and Li6PS5Cl 0.5 Br 0.5 One or more of the following; wherein 0.5≤i≤0.7, 0<j≤0.5.
[0020] Among them, due to Li 6-i P 1+j S 5-i Cl 1+i A higher phosphorus content in medium-sized lithium phosphate electrolytes is more conducive to the formation of a lithium phosphate protective layer; therefore, the phosphorus-containing sulfide solid electrolyte described in this disclosure is more preferably Li... 6-i P 1+j S 5-i Cl 1+i One or more of them.
[0021] In a second aspect, this disclosure provides a method for preparing a composite cathode material as described in the first aspect, the method comprising the following steps:
[0022] Under a protective atmosphere, lithium niobate-coated lithium nickel cobalt manganese oxide is mixed with a phosphorus-containing sulfide solid electrolyte and calcined to obtain the composite cathode material.
[0023] Through calcination, lithium niobate and phosphorus-containing sulfide solid electrolyte can react in situ to generate a lithium phosphate protective layer. This layer can suppress the interfacial reaction between lithium nickel cobalt manganese oxide and sulfide solid electrolyte, ensuring the stability of the structure and composition of lithium nickel cobalt manganese oxide. It can also uniformly coat the outside of lithium nickel cobalt manganese oxide with solid electrolyte, increasing the interfacial contact area and contact stability between the positive electrode active material and the solid electrolyte, and improving ion transport efficiency.
[0024] In some embodiments of this disclosure, the protective atmosphere is an argon atmosphere or a nitrogen atmosphere.
[0025] In some embodiments of this disclosure, the lithium niobate content in the lithium nickel cobalt manganese oxide coated with lithium niobate is 0.05-5 wt%; for example, it can be 0.05 wt%, 0.08 wt%, 0.1 wt%, 0.15 wt%, 0.2 wt%, 0.3 wt%, 0.4 wt%, 0.5 wt%, 0.8 wt%, 1 wt%, 1.5 wt%, 2 wt%, 2.5 wt%, 3 wt%, 3.5 wt%, 4 wt%, 4.5 wt%, or 5 wt%, etc.
[0026] In some embodiments of this disclosure, the mass ratio of lithium niobate-coated nickel-cobalt-manganese oxide to phosphorus-containing sulfide solid electrolyte is 70:30-80:20; for example, it can be 70:30, 72:28, 73:27, 75:25, 76:24, 78:22, or 80:20. If the amount of lithium niobate-coated nickel-cobalt-manganese oxide is too small and the amount of phosphorus-containing sulfide solid electrolyte is too large, it can easily lead to a low energy density of the battery; if the amount of lithium niobate-coated nickel-cobalt-manganese oxide is too large and the amount of phosphorus-containing sulfide solid electrolyte is too small, it can easily lead to a poor coating effect.
[0027] In some embodiments of this disclosure, the calcination temperature is 400-600℃; for example, it can be 400℃, 420℃, 450℃, 480℃, 500℃, 520℃, 550℃, 580℃ or 600℃, etc.
[0028] In some embodiments of this disclosure, the calcination time is 2-6 hours; for example, it can be 2 hours, 2.5 hours, 3 hours, 3.5 hours, 4 hours, 4.5 hours, 5 hours, 5.5 hours, or 6 hours.
[0029] In some embodiments of this disclosure, the heating rate of the calcination is 1-10℃ / min; for example, it can be 1℃ / min, 2℃ / min, 3℃ / min, 4℃ / min, 5℃ / min, 6℃ / min, 7℃ / min, 8℃ / min, 9℃ / min or 10℃ / min, etc.
[0030] In some embodiments of this disclosure, the preparation method further includes: after calcination, dispersing the product.
[0031] Thirdly, this disclosure provides an all-solid-state lithium battery, comprising the composite cathode material, solid electrolyte, and anode material described in the first aspect.
[0032] Compared with related technologies, this disclosure has the following beneficial effects:
[0033] This disclosure discloses a composite cathode material with stable structure and composition and high ion transport efficiency by combining a lithium niobate layer, a lithium phosphate layer, and a phosphorus-containing sulfide solid electrolyte layer. Specifically, by forming a lithium phosphate protective layer between the lithium niobate layer and the phosphorus-containing sulfide solid electrolyte layer, the interfacial reaction between lithium nickel cobalt manganese oxide and the sulfide solid electrolyte is suppressed, ensuring the stability of the structure and composition of lithium nickel cobalt manganese oxide. Furthermore, the solid electrolyte is uniformly coated on the outside of the lithium nickel cobalt manganese oxide, increasing the interfacial contact area and contact stability between the cathode active material and the solid electrolyte, thereby improving ion transport efficiency. This results in all-solid-state lithium batteries assembled using this composite cathode material exhibiting excellent rate performance and cycle stability. Attached Figure Description
[0034] Figure 1 X-ray diffraction pattern of the composite cathode material provided in Example 1;
[0035] Figure 2 X-ray diffraction pattern of the composite cathode material provided for Comparative Example 1;
[0036] Figure 3 X-ray diffraction pattern of the composite cathode material provided for Comparative Example 2;
[0037] Figure 4 The rate performance diagram of the all-solid-state lithium battery using the composite cathode material provided in Example 1;
[0038] Figure 5 The circuit performance diagram shows the all-solid-state lithium battery using the composite cathode material provided in Example 1.
[0039] Figure 6 The rate performance diagram of the all-solid-state lithium battery using the composite cathode material provided in Comparative Example 1;
[0040] Figure 7 The circuit performance diagram shows the all-solid-state lithium battery using the composite cathode material provided in Comparative Example 1. Detailed Implementation
[0041] The technical solution of this disclosure will be further described below with reference to the accompanying drawings and specific embodiments. Those skilled in the art should understand that the specific embodiments described are merely illustrative of this disclosure and should not be construed as limiting its scope.
[0042] Example 1
[0043] This embodiment provides a composite cathode material with a core-shell structure, comprising, from the inside out, LiNi. 0.6 Co 0.2 Mn 0.2 O2 particles, lithium niobate layer, lithium phosphate layer and Li 5.4 P1.1 S 4.4 Cl 1.6 Sulfide solid electrolyte layer.
[0044] The preparation method of this composite cathode material is as follows:
[0045] Weigh out the lithium niobate-coated LiNi at a mass ratio of 70:30. 0.6 Co 0.2 Mn 0.2 O2 positive electrode active material (containing 0.05wt% lithium niobate) and Li 5.4 P 1.1 S 4.4 Cl 1.6 The sulfide solid electrolyte was manually ground and mixed for 30 minutes. Under an argon atmosphere, the temperature was controlled at a rate of 2℃ / min and sintered at 400℃ for 4 hours. The product was then broken up to obtain a composite cathode material (D50 particle size of 50 micrometers).
[0046] Example 2
[0047] This embodiment provides a composite cathode material with a core-shell structure, comprising, from the inside out, LiNi. 0.6 Co 0.2 Mn 0.2 O2 particles, lithium niobate layer, lithium phosphate layer and Li 5.5 P 1.2 S 4.5 Cl 1.5 Sulfide solid electrolyte layer.
[0048] The preparation method of this composite cathode material is as follows:
[0049] Weigh out the lithium niobate-coated LiNi at a mass ratio of 72:28. 0.5 Co 0.3 Mn 0.2 O2 positive electrode active material (containing 0.1 wt% lithium niobate) and Li 5.5 P 1.2 S 4.5 Cl 1.5 The sulfide solid electrolyte was mixed by roller milling at 300 rpm for 50 minutes, and sintered at 450°C for 6 hours under an argon atmosphere with a controlled heating rate of 9°C / min. The product was then broken up to obtain the composite cathode material (D50 particle size of 30 micrometers).
[0050] Example 3
[0051] This embodiment provides a composite cathode material with a core-shell structure, comprising, from the inside out, LiNi. 0.8 Co 0.1 Mn 0.1O2 particles, lithium niobate layer, lithium phosphate layer and Li 5.3 P 1.3 S 4.3 Cl 1.7 Sulfide solid electrolyte layer.
[0052] The preparation method of this composite cathode material is as follows:
[0053] Weigh out the lithium niobate-coated LiNi at a mass ratio of 75:25. 0.8 Co 0.1 Mn 0.1 O2 positive electrode active material (containing 0.2wt% lithium niobate) and Li 5.3 P 1.3 S 4.3 Cl 1.7 The sulfide solid electrolyte was ball-milled at 300 rpm for 20 minutes, and then sintered at 500°C for 3 hours under a nitrogen atmosphere with a controlled heating rate of 5°C / min. The product was then broken up to obtain the composite cathode material (D50 particle size of 10 micrometers).
[0054] Example 4
[0055] This embodiment provides a composite cathode material with a core-shell structure, comprising, from the inside out, LiNi. 0.9 Mn 0.1 O2 particles, lithium niobate layer, lithium phosphate layer and Li 5.4 P 1.1 S 4.4 Cl 1.6 Sulfide solid electrolyte layer.
[0056] The preparation method of this composite cathode material is as follows:
[0057] Weigh out the lithium niobate-coated LiNi at a mass ratio of 78:22. 0.9 Mn 0.1 O2 positive electrode active material (containing 2wt% lithium niobate) and Li 5.4 P 1.1 S 4.4 Cl 1.6 The sulfide solid electrolyte was mixed by shaking at 500 times / min for 45 minutes, and then sintered at 550℃ for 5 hours under a nitrogen atmosphere with a controlled heating rate of 10℃ / min. The product was then dispersed to obtain the composite cathode material (D50 particle size of 5 micrometers).
[0058] Example 5
[0059] This embodiment provides a composite cathode material with a core-shell structure, comprising, from the inside out, LiNi. 0.98 Mn 0.02 O2 particles, lithium niobate layer, lithium phosphate layer and Li5.4 P 1.1 S 4.4 Cl 1.6 Sulfide solid electrolyte layer.
[0060] The preparation method of this composite cathode material is as follows:
[0061] Weigh out the lithium niobate-coated LiNi at a mass ratio of 80:20. 0.98 Mn 0.02 O2 positive electrode active material (containing 5wt% lithium niobate) and Li 5.4 P 1.1 S 4.4 Cl 1.6 The sulfide solid electrolyte was manually ground and mixed for 1 hour. Under a nitrogen atmosphere, the temperature was controlled at a rate of 1℃ / min and sintered at 600℃ for 2 hours. The product was then broken up to obtain a composite cathode material (D50 particle size of 2 micrometers).
[0062] Example 6
[0063] This embodiment provides a composite cathode material, the only difference between its preparation method and that of Example 3 is that Li... 5.3 P 1.3 S 4.3 Cl 1.7 The sulfide solid electrolyte was replaced with β-Li3PS4.
[0064] Example 7
[0065] This embodiment provides a composite cathode material, the only difference between its preparation method and that of Example 3 is that Li... 5.3 P 1.3 S 4.3 Cl 1.7 The sulfide solid electrolyte was replaced with Li7P2S8I.
[0066] Comparative Example 1
[0067] This comparative example provides a composite cathode material whose preparation method differs from that of Example 1 only in that the composite cathode material is obtained directly without sintering after manual grinding and mixing for 30 minutes.
[0068] Comparative Example 2
[0069] This comparative example provides a composite cathode material, the only difference between its preparation method and that of Example 1 being the use of lithium niobate-coated LiNi. 0.6 Co 0.2 Mn 0.2 The O2 positive electrode active material (containing 0.05 wt% lithium niobate) is replaced with lithium lanthanum zirconium oxide (Li7La3Zr2O) 12 LiNi coated with LLZO0.6 Co 0.2 Mn 0.2 O2 positive electrode active material (containing 0.05wt% lithium lanthanum zirconium oxide).
[0070] Comparative Example 3
[0071] This comparative example provides a composite cathode material, the only difference between its preparation method and that of Example 1 being the use of lithium niobate-coated LiNi. 0.6 Co 0.2 Mn 0.2 The O2 positive electrode active material (containing 0.05 wt% lithium niobate) was replaced with lithium phosphate-coated LiNi. 0.6 Co 0.2 Mn 0.2 O2 positive electrode active material (containing 0.05wt% lithium phosphate).
[0072] X-ray diffraction characterization:
[0073] The composite cathode materials provided in Example 1, Comparative Example 1, and Comparative Example 2 were characterized using X-ray diffraction, and the results are as follows: Figure 1 , Figure 2 and Figure 3 As shown.
[0074] from Figure 1 It can be seen that lithium phosphate was generated in the composite cathode material provided in Example 1; from Figure 2 It can be seen that in Comparative Example 1, because sintering was not performed, lithium niobate did not react with the sulfide solid electrolyte, and no lithium phosphate was produced; from Figure 3 It can be seen that in Comparative Example 2, lithium lanthanum zirconium oxide did not react with the sulfide solid electrolyte to produce lithium phosphate.
[0075] Electrochemical performance testing:
[0076] The composite cathode material provided in the above embodiments and comparative examples was pressed onto the Li6PS5Cl solid electrolyte layer under a pressure of 180MPa to obtain a cathode sheet in which the composite cathode material layer and the electrolyte layer are tightly bonded. Then, a current collector was pressed onto the composite cathode material layer of the cathode sheet. After placing a lithium indium alloy layer and a current collector on the other side of the electrolyte layer, the cathode sheet was pressed to obtain an all-solid-state lithium battery.
[0077] The all-solid-state lithium battery was tested under the conditions of charge / discharge voltage of 2.4V-3.7V, pressure of 90MPa, and room temperature. The initial charge / discharge efficiency (0.1C), rate performance of 0.1-1C, and charge / discharge cycle performance at 1C were tested. The results are shown in Tables 1 and 2 below.
[0078] Table 1
[0079]
[0080]
[0081] Table 2
[0082]
[0083]
[0084] The rate performance and cycle performance of the all-solid-state lithium battery using the composite cathode material provided in Example 1 are as follows: Figure 4 and Figure 5 As shown in the figure. The rate performance and cycle performance of the all-solid-state lithium battery using the composite cathode material provided in Comparative Example 1 are as follows. Figure 6 and Figure 7 As shown. Figure 4 and Figure 5 In the middle, the multiplier is 0.1C for laps 2-6, 0.2C for laps 7-11, 0.3C for laps 12-16, and 1C for laps 17-21.
[0085] From the experimental results in Tables 1 and 2, and Figures 4-7 It can be seen that the all-solid-state lithium battery using the composite material provided in this disclosure has good rate performance and cycle performance. Compared with Example 1, Comparative Example 1 did not undergo sintering, and Comparative Example 2 used lithium nickel cobalt manganese oxide coated with lithium lanthanum zirconium oxide instead of lithium nickel cobalt manganese oxide coated with lithium niobate. Neither of these two examples produced a lithium phosphate protective layer, resulting in a significant decrease in the rate performance and cycle performance of the all-solid-state lithium battery using them. Although Comparative Example 3 directly used lithium nickel cobalt manganese oxide coated with lithium phosphate, the contact between the electrolyte layer and the active material was poor, resulting in poor rate performance and cycle performance of the all-solid-state lithium battery assembled with it.
[0086] The above description is merely a specific embodiment of this disclosure, enabling those skilled in the art to understand or implement it. Various modifications to these embodiments will be readily apparent to those skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of this disclosure. Therefore, this disclosure is not to be limited to the embodiments described herein, but is to be accorded the widest scope consistent with the principles and novel features disclosed herein.
Claims
1. A composite cathode material, characterized in that, The composite cathode material has a core-shell structure, comprising, from the inside out, lithium nickel cobalt manganese oxide particles, a lithium niobate layer, a lithium phosphate layer, and a phosphorus-containing sulfide solid electrolyte layer; the lithium phosphate layer is generated by in-situ reaction of lithium niobate and phosphorus-containing sulfide solid electrolyte.
2. The composite cathode material according to claim 1, characterized in that, The lithium nickel cobalt manganese oxide is selected from LiNi m Co n Mn 1-m-n One or more of O2; Where 0.5≤m<1, 0.5≤m+n≤1.
3. The composite cathode material according to claim 1 or 2, characterized in that, The phosphorus-containing sulfide solid electrolyte is selected from x(Li) a G)·y(T c D d One or more of )·z(P2S5); Where 0 ≤ x < 100, 0 ≤ y < 100, 0 ≤ z < 100; a = 1 or 2, c = 1 or 2, d = 1, 2 or 5; Element G is S, Cl, Br, or I; Element T is Li, Si, Ge, P, Sn, or Sb; Element D is Cl, Br, I, O, S, or Se; And Li a G, T c D d Unlike P2S5, the stoichiometry of Li, P, and S is not zero.
4. The composite cathode material according to claim 3, characterized in that, The phosphorus-containing sulfide solid electrolyte is selected from Li 6-i P 1+j S 5-i Cl 1+i One or more of Li6PS5Cl, β-Li3PS4, Li7P2S8I and Li6PS5ClBr; wherein 0.5≤i≤0.7, 0<j≤0.
5.
5. The composite cathode material according to claim 4, characterized in that, The phosphorus-containing sulfide solid electrolyte is selected from Li 6-i P 1+j S 5-i Cl 1+i One or more of them.
6. A method for preparing a composite cathode material as described in any one of claims 1-5, characterized in that, The preparation method includes the following steps: Under a protective atmosphere, lithium niobate-coated lithium nickel cobalt manganese oxide is mixed with a phosphorus-containing sulfide solid electrolyte and calcined to obtain the composite cathode material.
7. The preparation method according to claim 6, characterized in that, The protective atmosphere is an argon atmosphere or a nitrogen atmosphere.
8. The preparation method according to claim 6, characterized in that, The lithium niobate content in the lithium nickel cobalt manganese oxide coated with lithium niobate is 0.05-5 wt%.
9. The preparation method according to claim 6, characterized in that, The mass ratio of lithium niobate-coated nickel cobalt manganese oxide to phosphorus-containing sulfide solid electrolyte is 70:30-80:
20.
10. The preparation method according to claim 6, characterized in that, The calcination temperature is 400-600℃.
11. The preparation method according to claim 6, characterized in that, The calcination time is 2-6 hours.
12. The preparation method according to claim 6, characterized in that, The heating rate for calcination is 1-10℃ / min.
13. The preparation method according to claim 6, characterized in that, The preparation method further includes: after calcination, dispersing the product.
14. A fully solid-state lithium battery, characterized in that, It includes the composite positive electrode material, solid electrolyte, and negative electrode material as described in any one of claims 1-5.
Citation Information
Patent Citations
Positive electrode material and battery
CN115443555A